HOW TO MAINTAIN GOING CONCERN AMONG MSME IN POST-PANDEMIC ERA - Suratman, Sasa; Aisyah, Isye; Septiawan, Budi (Jurnal Riset Bisnis dan Manajemen, 2023)
After the Covid-19 pandemic is a phase where the business world is full of uncertainty, MSME are also affected by the going concern of their business. MSME need to make efforts to be able to maintain their business. This study is necessary, because it aims to find out what factors influence going concern in the MSME sector in the post-pandemic era. This research was conducted in Kadungora District, Garut Regency and the number of MSME involved in this study was 115. The research method was by survey and using the SmartPLS application as a tool for analyzing data. The results of the research show that e-commerce adoption had no impact on MSME’s going concern. Meanwhile, human capital and accounting information systems can influence going concern in MSME.